Plea bargaining system : da culpa voluntária ao fim do rule of law no sentenciamento criminal - Santander, Juan Marcel Montiel (2021)
This paper aims to analyze the historical systematization of the plea bargaining and how the concepts of voluntariness and coercion suffer a huge erosion in the principle bases of the judgment procedure with its slow and constant progress. Furthermore, it is commonly understood that the advancement of plea bargaining under enormous rates of adjudication in the criminal area is, consequently, an occurrence of the systems of common law, in view of their own procedural conditions, which for now, presents itself in the international scope with the highest award rates for assumption of guilt and waives judgment. The research sought to clarify the presence of ancestral negotiating institutes in criminal proceedings, with plea bargaining being its last and systematized formulation, demonstrating its presence already in the canonical procedure and in medieval English. From the development of the adversarial system, a direct result of the Glorious Revolution, as well as from a terrifying legislation formulated by an aristocracy that sought to instill order in a mass of English without property of the century. XVIII, the research seeks to clarify the presence of the bargain, initially, through a correctional ideal through a lenient penalty, avoiding the capital execution. Its systematization takes place under the conditions of the United States of the century XIX, with its malleability and wide appeal restriction, in principle, of this “procedural corruption”, where in face of the context of the century. XX, its use has become a logic that never stopped deepening. In addition, the research carried out is applied on an exploratory basis, using a bibliographic and documentary review, based on plea bargaining, criminology and American sociology and the works of criminal proceedings under the common law and civil law systems. The present work is linked to the Research Line of Contemporary Legal and Criminal Systems of the Master in Criminal Sciences at the School of Law of the Pontifical Catholic University of Rio Grande do Sul - PUCRS.